Counting and Measuring: a theoretical and crosslinguistic account - Susan Rothstein (Baltic International Yearbook of Cognition, Logic and Communication, 2016)
In this paper, I show that expressions like two glasses of wine are ambiguous between counting and measuring interpretations, and that each interpretation is associated with a different semantic representation. In each interpretation, glasses has a different function. In the counting interpretation, glasses is a relational noun, while in the measure interpretation, glasses is a measure head analogous to litre. This difference leads to a number of grammatical contrasts which can be explained by differences in the grammatical structure. I discuss whether these differences are only semantic or also expressed in the syntactic representation. The assumption that syntax directly reflects semantic interpretation leads to assigning counting NPs and measuring NPs two different syntactic structures: counting NPs are right-branching with two modifying glasses of wine, while in measure expressions the numeral and the measure head form a measure predicate two glasses which modifies the N. I show that in Modern Hebrew and Mandarin counting structures and measuring structures clearly do have different syntactic structures, reflecting the semantic differences between counting and measuring. While the evidence in the case of English is less strong, the assumption that syntax directly reflects compositional syntactic structure results in the same basic syntactic contrasts in English as well.
Keywords: counting; measuring; linguistics; syntactic interpretation; semantic interpretation